Prediction of Stock Option Prices Using Volatility (Garch (1, 1)) Adjusted Black Scholes Option Pricing Model - Pradeep Kumar, G.; Saravanan, S. (Indian Journal of Finance, 2013)
This paper attempts to predict the option prices for the future date using the adjusted volatility to the traditional Black-Scholes option pricing model using GARCH (1, 1) in pricing the stock option contracts for the selected eight companies. The study uses the Black-Scholes model along with its basic parameters and the best known time series model GARCH (1, 1) for predicting volatility in order to estimate the future stock option contract prices. This helps in knowing how the prices of stocks would be in the near future. The study finally attempts to identify the pricing errors between the market price of the option contracts and the calculated option prices. This is done with the help of mean absolute percentage error and mean absolute deviation tools. The results of the study indicate that there was only a small difference between the calculated prices and the market price of the option contracts.